Development of protective protein emulsion technology for mechanically deboned poultry meat - Онищенко, В’ячеслав Миколайович; Гринченко, Наталя Геннадіївна; Большакова, Вікторія Анатоліївна (Eastern-European Journal of Enterprise Technologies, 2014)
Using mechanically deboned poultry meat (MPMO) to sell as mincemeat or recipe ingredient has a number of negative aspects that lie in the oxidation and microbiological stability reduction, caused by production factors and biochemical properties of such raw product as a result of the transition of bone marrow lipids and hemoproteins. On this basis, the paper is aimed at using protective protein emulsions (PPE) that contain mostly natural components and allow to some extent eliminate the negative impact of phospholipid compounds, heme pigments and so on. The results of the design and scientific substantiation of technological solutions that allow to increase the functional and technological and improve consumer properties of mechanically deboned poultry meat (chicken) by adding the PPE, protein preparation from pork skin ScangelA95, sodium ascorbyl palmitate antioxidant are given in the paper. It was found that introducing the proposed PPE leads to increased shear stress limit, reduced intensity of a specific dirty red color of MDPM towards pale red and pink, approximating color to characteristic for minced chicken from shin muscles, loss of gloss and matte appearance, improved mincemeat stability, which lies in reduced oxidation product formation intensity.